IMPROVING STUDENTS’ CRITICAL READING ABILITY: COOPERATIVE LEARNING STRATEGY (A CASE STUDY IN ENGLISH STUDY PROGRAM BRAWIJAYA UNIVERSITY) - Sudarwati, Emi; Manipuspika, Yana Shanti (ELTICS : Journal of English Language Teaching and English Linguistics, 2017)
This study deals with a strategy named Group Discussion model of Cooperative Learning strategy applied in the teaching of Critical Reading course at English Study Program, Brawijaya University. By using that strategy, it is expected that the problem in Critical Reading class can be solved and students’ ability in critical reading will, in turn, be improved. The design of the study is Classroom Action Research (CAR) since the study is aimed at improving the students’ critical reading ability and solving the classroom’s problems on the teaching of reading. Based on its characteristics, the classroom action research is done repeatedly until those problems can be solved. Dealing with the classroom setting, the study is directed to develop the teaching strategy in order to find out a solution to the classroom’s problem in the teaching of reading. This study reveals that Cooperative Learning strategy has successfully improved students’ critical reading ability. In doing so, there are stages conducted namely, having cooperative work organization, using appropriate media, having creativity (for teachers), monitoring teaching and learning processes closely, and giving students feedback on their work. In conclusion, Cooperative Learning can be beneficial for students’ learning in critical reading as it can make students active and enjoy the classroom activities. However, it also has weaknesses such as time consuming and less appropriate for classes with bigger number of students. Despite the weaknesses, teachers are still recommended to apply this strategy in critical reading classes. Key words: critical reading, cooperative learning, Group Discussion, Classroom Action Research (CAR)